MULTILINGUALISM IN THE AGE OF GLOBALISATION: PROBLEMS AND EFFECTIVE STRATEGIES FOR PERSONALITY FORMATION - T.V. Pitirimova (Многоязычие в образовательном пространстве, 2024)
With the rapid development of globalisation and intercultural interaction, multilingualism is becoming a key element of successful social adaptation and professional development. However, the formation of a multilingual personality is subject to several difficulties, ranging from a lack of motivation to the difficulties in integrating different linguistic structures. Research in this field becomes relevant to develop effective learning strategies and to maximise the benefits of multilingualism in today’s world. This study aims to identify the challenges faced by learners in the process of developing a multilingual identity and to develop practical methods to address them. The methodology includes analysing learners’ motivation, exploring language environments for practice and applying integrated educational techniques. It is found that the main problem is the lack of clear motivation for learning multiple languages. Motivational programmes have been developed to stimulate interest and understanding of the benefits of multilingualism. The analysis has shown that the lack of a suitable language environment can slow down the learning process. Recommendations for creating virtual and real language communities for effective practice are offered. Integrated teaching techniques proved to be an effective way of minimising the conflict between language structures. Curricula have been developed to facilitate the coordinated learning of multiple languages. The results of the study emphasise the importance of an integrated approach to developing a multilingual personality. Our recommendations include the introduction of motivational programmes, the creation of language environments and the use of integrated techniques in educational practice. The practical significance of the study lies in creating more effective educational strategies to support multilingualism in today’s society. Further research should focus on adapting the methodologies to specific sociocultural contexts and developing technological solutions to support this process.